Optimization of Coffee-Clove-Ginger Formulated Powder Based on Antioxidant Activity and Physicochemical Properties - Arisa Puji Lestari; Siti Susanti; Anang Mohamad Legowo (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2018)
The development of coffee products as functional drinks is hoped to increase the popularity of coffee as a healthy drink. One way of improving is by adding spices into the coffee. The objective of this research was to obtain optimization of coffee-spice formulated powder based on its antioxidant activity, water content, ash content, and extract content. The spices used in this research were ginger powder and cloves(1:1). In this research, the ratio of coffee:spices (%,b/b) tested varied with F0(100%: 0%), F1(95%: 5%), F2(90%:10%), F3(85%:15%), and F4(80%:20%) each ratios underwent 4 repetitions of tests. F0-F4 was roasted for 35 minutes at 20 °C. The results showed that all formulas except F4 had met the SNI certifications of ground coffee. F1 had the lowest(p<0.05) water(5.58%) and ash content(4.63%), while its extract content(29.68%) was the highest(p<0.05) out of all the other varying ratios of coffee: spices formula (F1-F4). There was no significant difference between F1 and F0(100% coffee). F4 had the lowest IC50(21.62μg/mL) among other formulas. Thus the formula with the lowest proportion of spices was considered as the optimal formula based on the water content, ash content, and extract content, whereas of antioxidant status, the formula with the highest proportion of spices was considered the best formula. The more the proportion of spices in the formula, the better the antioxidant status, but less optimum in terms of its other chemical properties. It is hoped that the spiced coffee formula could potentially serve as a functional beverage for the community.